THE CRITERIA FOR PROSPECTIVE LIFE PARTNERS IN FORMING A FAMILY OF SAKINAH MAWADDAH WAROHMAH ACCORDING TO COMMUNITY LEADERS OF PANANCANGAN VILLAGE (CASE STUDY IN CIPOCOK JAYA DISTRICT) - Ahmad Sarmadi; Syarif Hidayatullah; Bambang Setyawan (EKOSSISTEM : Islamic Economics, Banking, Law, System, 2025)
The family of Sakinah Mawaddah Warahmah is the dream of every Muslim, but the reality of the high divorce rate indicates the need for careful consideration in choosing a life partner. This study aims to criticize and uncover the criteria for prospective life partners according to the perspective of local wisdom of community leaders in Panancangan Village, Cipocok Jaya District. This qualitative case study collected data through in-depth interviews with religious leaders, traditional leaders, and parents who were considered successful in fostering households, as well as observations and document studies. The data were analyzed interactively using the Miles and Huberman models. The results of the study form a hierarchical-integrative framework of criteria, consisting of: (1) the foundation of religion and morals as the central axis and value filter, (2) psychological and mental readiness as a tool for navigating relationships, (3) economic and social aspects as a support for household operational stability, and (4) education and insight as a driver of adaptation and family development. These four pillars synergize dynamically with each other, representing a holistic model that blends spiritual idealism with social reality to realize family resilience.